Leaders and Health Care Organizational Change Art, Politics and Process - Gabel, Stewart (Springer US, 2001)
Health and mental health organizations are undergoing major changes in policies, procedures, structures, and emphasis. Many of these changes appear related to what may be termed the managed care revolution. This upheaval in delivery systems related to health and mental health care has been associated with great changes and rapid turnover in leaders and in leadership positions. It appears that many leaders are not able to lead their organizations into this or other new territories. The purpose of this book is to describe stages that organizations go through as they move rapidly to adapt to new and sometimes unwanted changes. The emphasis is on the aspects of leaders and of leadership that appear tied to successful or unsuccessful outcomes for organizations in the midst of these rapid changes. Particular challenges and expectations that are likely to be present in organizations and in individuals facing change are described. Methods are presented that might be employed by leaders to confront various difficulties in order to direct successful outcomes for themselves, as leaders, and for their organizations. Throughout the book, the essential and sometimes differing goals of leaders as individuals and of leadership as a professional process are highlighted. This book will be of interest to leaders and managers at all levels in various health and mental health care organizations, as well as graduate students in health care management, health care services, health care administration, and business administration. It will also be of interest to mental health professionals and graduate students in industrial and organizational psychology
Keywords: Public Health; Management; Health Informatics; Medical records / Data processing